In Entamoeba histolytica, a BspA family protein is required for chemotaxis toward tumour necrosis factor - Anne Silvestre; Aurélie Plaze; Patricia Berthon; Roman Thibeaux; Nancy Guillen; Elisabeth Labruyère (Microbial Cell)
Background: Entamoeba histolytica cell migration is essential for the development of human amoebiasis (an infectious disease characterized by tissue invasion and destruction). The tissue inflammation associated with tumour necrosis factor (TNF) secretion by host cells is a well-documented feature of amoebiasis. Tumour necrosis factor is a chemoattractant for E. histolytica, and the parasite may have a TNF receptor at its cell surface. Methods: confocal microscopy, RNA Sequencing, bioinformatics, RNA antisense techniques and histological analysis of human colon explants were used to characterize the interplay between TNF and E. histolytica. Results: an antibody against human TNF receptor 1 (TNFR1) stained the E. histolytica trophozoite surface and (on immunoblots) binds to a 150-kDa protein. Proteome screening with the TNFR1 sequence revealed a BspA family protein in E. histolytica that carries a TNFR signature domain and six leucine-rich repeats (named here as "cell surface protein", CSP, in view of its cellular location). Cell surface protein shares structural homologies with Toll-Like receptors, colocalizes with TNF and is internalized in TNF-containing vesicles. Reduction of cellular CSP levels abolished chemotaxis toward TNF and blocked parasite invasion of human colon. Conclusions: there is a clear link between TNF chemotaxis, CSP and pathogenesis.